JOURNAL OF GOVERNMENT & POLITICS : The Quality of Higher Education in Public Administration in Thailand : the Side-Effects of Administrative Reform - Amporn Tamronglak (FISIPOL UMY, 2016)
Since the current quality framework, called Thailand Qualification Frameworks for Higher Education Commission (OHEC), the quality of the graduates produced and the quality of teaching Public Administration particularly graduates study seems to be in the opposite directions.